2005
DOI: 10.1039/b507765f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-promoted Co–Cu catalyst for highly efficient synthesis of higher alcohols from syngas

Abstract: The development of a type of carbon-nanotube-promoted Co-Cu catalyst, which displays excellent performance for highly effective and selective formation of the C(2-4)-oxygenates, especially BuOH and DME, from syngas, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Moreover, the H-adspecies with higher stationary-state concentration at the surface of functioning catalyst would be in favor of inhibiting water-gas shift side-reaction, contributing considerably to an increase in the product yields. These are very similar to the cases of methanol synthesis over the MWCNT-promoted Cu-ZnO-Al 2 O 3 catalyst [8,9] and of higher alcohol synthesis over the MWCNT-promoted Co i Cu j catalyst [10].…”
Section: H 2 (Or Co)-tpd Characterization Of the Supports And The Presupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the H-adspecies with higher stationary-state concentration at the surface of functioning catalyst would be in favor of inhibiting water-gas shift side-reaction, contributing considerably to an increase in the product yields. These are very similar to the cases of methanol synthesis over the MWCNT-promoted Cu-ZnO-Al 2 O 3 catalyst [8,9] and of higher alcohol synthesis over the MWCNT-promoted Co i Cu j catalyst [10].…”
Section: H 2 (Or Co)-tpd Characterization Of the Supports And The Presupporting
confidence: 78%
“…Catalytic applications range from selective hydrogenation of a,b-unsaturated aldehydes [4], hydrofomylation of alkenes [5], ammonia synthesis [6], Fischer-Tropsch synthesis [7], methanol and higher alcohol synthesis [8][9][10], to dehydrogenation of alcohols [11], oxidation [12] and electrocatalysis [13], etc. The catalytic studies conducted so far on MWCNT-based systems have shown promising results in terms of activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The conditioning of reduced catalysts with CO 2 at elevated temperature (e.g., 200°C) has been applied to the passivation of Ni-Cr/Al 2 O 3 steam-reforming-methanation catalysts [51]. Furthermore, the XPS and XRD data of Cu-based [52] and Cu-Co-based [53] catalysts that had been exposed to CO/CO 2 -containing gas mixtures during the synthesis of alcohols are relevant also to passivation. Metallic copper and Cu 2 O were identified by XRD for a Cu-ZnO-Al 2 O 3 catalyst after use in methanol synthesis [52].…”
Section: Methods Combining Carbon and Oxide Formationmentioning
confidence: 99%
“…However, we suggest to assign the corresponding XPS spectra to Cu(1+) rather than to Cu(0) or a mixture of both species, in agreement with literature [48,54] and the well-known instability of Cu(0) in oxidizing atmosphere (i.e., air). For the Cu-Co-based catalysts used in the synthesis of higher alcohols, metallic Co as well as oxidized Co species were identified by XPS [53].…”
Section: Methods Combining Carbon and Oxide Formationmentioning
confidence: 99%
“…Recent studies revealed that both the activity and selectivity to higher alcohols can be improved by adding effective promoters, such as Fischer-Tropsch components and alkali metals into MoS 2 -based catalysts [1][2][3][4][5], changing the nature of the catalyst supports [6][7][8][9][10][11], and modifying the catalyst preparation method [12,13]. Very recently, other new catalysts were also developed and a good activity and selectivity could also be obtained.…”
Section: Introductionmentioning
confidence: 99%